2022
DOI: 10.7150/thno.77281
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell atlases link macrophages and CD8+ T-cell subpopulations to disease progression and immunotherapy response in urothelial carcinoma

Abstract: Rationale: Immune checkpoint inhibitors (ICIs) have revolutionized the management of locally advanced or metastatic urothelial carcinoma. Strikingly, compared to urothelial carcinoma of the bladder (UCB), upper tract urothelial carcinoma (UTUC) has a higher response rate to ICIs. The stratification of patients most likely to benefit from ICI therapy remains a major clinical challenge. Methods: In this study, we performed the first single-cell RNA sequencing (scRNA-seq) study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Therefore, we turned to the Senmayo gene set 41 which exhibited the excellent evaluation for cellular senescence and observed significant senescent signatures exclusively in Mbm cells, which helps explain the functional defects around scaffolds in aged wounds. However, type L immune response-associated CD4+ Th_naïve did not show the cellular senescence 79 , and its functional defects may be attributed to the local cell-cell communications with corresponding Mbm. Through CellChat analysis, the differential pathway expression from Mbm to Th_naïve further supported the initial speculation.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, we turned to the Senmayo gene set 41 which exhibited the excellent evaluation for cellular senescence and observed significant senescent signatures exclusively in Mbm cells, which helps explain the functional defects around scaffolds in aged wounds. However, type L immune response-associated CD4+ Th_naïve did not show the cellular senescence 79 , and its functional defects may be attributed to the local cell-cell communications with corresponding Mbm. Through CellChat analysis, the differential pathway expression from Mbm to Th_naïve further supported the initial speculation.…”
Section: Discussionmentioning
confidence: 87%
“…In recent years, the host tumor’s local immune response has gradually become a hot research topic [ 25 27 ]. Tumor-infiltrating immune cells play a crucial role in this response, and TILs make up the majority of this immune cell [ 27 , 28 ]. TILs, tumor-infiltrating lymphocytes, are a crucial part of the tumor microenvironment and lymphocytes that leave the bloodstream to infiltrate the tumor.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Meanwhile, the exhausted T cells and immunosuppressive macrophages exhibited enhanced interactions in urothelial carcinoma of the bladder and performed significant functions in antitumor immunotherapy. 28 Deletion of sorting nexin 9 (SNX9) in CD8+ T cells reduces the exhaustion of CD8+ T cells and enhances both T memory cell differentiation and interferon‐γ (IFNγ) secretion of adoptively transferred T cells, thereby enabling effective CAR‐T cells immunotherapy. 29 In addition, the differentiation and modulation of T(H) subpopulations as well as γδ T cells in the TIME is critical for cancer immunotherapy efficacy.…”
Section: Relationship Between Immune Cell and Cancer Immunotherapymentioning
confidence: 99%
“…Recent studies have revealed that T cells associated with recognizing cancer‐independent antigens (“bystander T cells”) also perform important functions in cancer immunotherapy and they differ in specificity, activation state, and effector function 27 . Meanwhile, the exhausted T cells and immunosuppressive macrophages exhibited enhanced interactions in urothelial carcinoma of the bladder and performed significant functions in antitumor immunotherapy 28 . Deletion of sorting nexin 9 (SNX9) in CD8+ T cells reduces the exhaustion of CD8+ T cells and enhances both T memory cell differentiation and interferon‐γ (IFNγ) secretion of adoptively transferred T cells, thereby enabling effective CAR‐T cells immunotherapy 29 .…”
Section: Relationship Between Immune Cell and Cancer Immunotherapymentioning
confidence: 99%